Multicultural Coexistence Migran Brazil di Hamamatsu, Jepang, sebagai Respon terhadap Krisis Ekonomi Global 2008 - Henny Rosalinda (Department of International Relations, Brawijaya University, 2014)
Abstract The research aims to investigate the effect of the 2008 economic crisis on the Brazilian migrant who are of Japanese descendants (Nikkeijin or Nikkei) in Hamamatsu Shizuoka Province, Japan. The global economic crisis in 2008 has caused socio-economic consequences. The research method was conducted by using literature reviews, interviews, and direct observation in the field which can be grouped under three main topics: multicultural policy (Hamamatsu City Hall International Section; Multicultural Centre), education (Collegio Pitagoras, Mundo de Alegria; Foreign Resident Study Support Centre; Catholic Hamamatsu Church), and responses of Nikkei (NPO Brazil Fureiai-kai; Servitu Import Shop).The result shows that as a direct consequence of the global financial crisis of 2008, up to 60% of Nikkei workers in Hamamatsu have found themselves unemployed and in a considerably unstable financial condition. This has resulted in the loss of educational opportunities for the children of the Nikkei. Consequently, future prospect of employmentfor their children becomes severe and this runs the risk of becoming a vicious cycle for the generations to come. Keywords: economic crisis 2008, migrant worker, multicultural coexistence